Experimental Study on Thermal Performance of Loop Heat Pipe with Flat-Rectangular Evaporator Under Gravity Assisted Condition - Hien Phuoc Huynh; Htoo Zin Kyaw; Keishi Kariya; Akio Miyara (EPI International Journal of Engineering, 2018)
In company with extreme developments of electronic devices, there are some unavoidable challenges to the conventional cooling methods such as high heat dissipation, limitation of cooling space, reliable operation as well as saving energy consumption. Therefore, the necessity of studying on new or how to improve the existing technologies is undoubted. Among various methodologies, the loop heat pipe (LHP) whose operation principle base on phase changing process, can be considered as one of the potential solutions of modern electronics cooling. This paper introduces the experimental investigation on the thermal performance of a flat-rectangular evaporator LHP with sintered stainless-steel wick when functioning under gravity assisted condition. Working fluid of this LHP was water. The present LHP could maintain stable operation in the range of heating power from 50 W to 520 W and keep the temperature on the heater’s top surface at 85oC, commonly recommended as the limitation temperature of electronics, when heating power reaches value 350 W (129.6 kW/m2). Besides, when turning the heater off, it took about 15 minutes for the LHP to cool the heating block from 102oC to 37oC. In addition, an assumption of the boiling heat transfer is introduced in this paper to explain the performance of evaporator at different heat flux conditions of the experiment.